Story of paper: save paper, save trees. THink smart, reuse it! - Sen, Benita (New Delhi The Energy Resources Institute, 2014)
What$1 (Bs common between a cardboard box and the tissues inside it? They are both made of paper! But have you ever wondered where paper comes from? The Story of Paper takes you on a paper trail, from mulberry bark and bamboo fibres to the textbook on your desk! However, producing more and more paper is harming our planet and causing pollution, because making paper involves cutting too many trees and using a lot of water and electricity. So we need to think sharp and be paper smart!s
Keywords: Paper